The last stand : Custer, Sitting Bull, and the Battle of the Little Bighorn - Philbrick, Nathaniel (New York : Viking, 2010)
The bestselling author of "Mayflower" sheds new light on one of the iconic stories of the American West, reminding readers that the Battle of the Little Bighorn was also, even in victory, the last stand for the Sioux and Cheyenne Indian nations.
At the flood -- The dream -- Hard ass -- The dance -- The scout -- The blue pencil line -- The approach -- The crow's nest -- Into the valley -- Reno's charge -- To the hill -- Still point -- The forsaken -- Grazing his horses -- The last stand -- The river of nightmares -- Epilogue: Libbie's house.
Includes bibliographical references (p. 419-446) and index.
Montana Book Award
Keywords: Little Bighorn, Battle of the, Mont., 1876.; Custer, George A. -- 1839-1876.; Sitting Bull, -- 1831-1890.; Dakota Indians -- Wars, 1876.